Модернізація економіки старопромислових регіонів на засадах smart-спеціалізації (за матеріалами наукового повідомлення на засіданні Президії НАН України 11 березня 2020 р.) - Петрова, І.П. (Вісник НАН України, 2020)
Оцінено сучасний стан і тенденції розвитку промисловості Дніпропетровської, Донецької, Запорізької та Луганської областей України. Визначено перспективи неоіндустріальної модернізації економіки старопромислових
регіонів на засадах smart-спеціалізації. Проаналізовано інституційне середовище регіонального розвитку цих областей. Запропоновано запровадити систему інститутів сприяння регіональному розвитку на засадах
smart-спеціалізації. Обґрунтовано необхідність застосування публічно-приватного партнерства для прискорення неоіндустріалізації. The current state and tendencies of industrial development of the old industrial regions of Ukraine are evaluated. Decreased
industrial production volume, decreased investment in production, lack of financial resources, low competitiveness
in world markets, increased dependence on imports are the reasons for which these regions are the least resistant to
various destabilizing factors. Prospects of neo-industrial modernization of the economy of the old industrial regions on
the basis of smart specialization are determined.
The institutional environment for regional development of the old industrial regions is analyzed. Formally, many institutes
for the development of old industrial regions have been established in Ukraine, but their activity lacks necessary
consistency and relevance to the specific conditions of development of such regions. The implementation of the smart
specialization strategy actualizes the formation and development of a system of institutions promoting regional development.
It is proposed to introduce a system of regional development assistance institutes according to the NUTS level nomenclature
of EU territorial units: smart economic district (NUTS-1), smart area (NUTS-2), smart city (NUTS-3),
smart-community (NUTS-4 (LAU-1), NUTS-5 (LAU-2)).
The necessity of using public-private partnership to accelerate neo-industrialization as an institutional innovation
that combines modernization of investment activity and of the mechanism of economic management is substantiated.